Cultural Politics and the Transatlantic Divide over GMOs - Stephan, H.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Alongside other factors, cultural values and identities help to explain different regulatory frameworks for genetically modified organisms. This book uses insights from environmental history and sociology to illuminate the cultural politics of regulation in the US and the EU, with particular attention to public opinion and anti-GMO activism.
Keywords: Sustainable development; Environmental geography; Environmental policy; Environmental economics; Environmental law; Sustainable Development; Environmental Geography; Environmental Politics; Environmental Economics; Environmental Law/Policy/Ecojustice.